2021
DOI: 10.1007/s10753-021-01490-3
|View full text |Cite
|
Sign up to set email alerts
|

Blocking SphK1/S1P/S1PR1 Signaling Pathway Alleviates Lung Injury Caused by Sepsis in Acute Ethanol Intoxication Mice

Abstract: Acute ethanol intoxication increases the risk of sepsis and aggravates the symptoms of sepsis and lung injury. Therefore, this study aimed to explore whether sphingosine kinase 1 (SphK1)/sphingosine-1-phosphate (S1P)/S1P receptor 1 (S1PR1) signaling pathway functions in lung injury caused by acute ethanol intoxication-enhanced sepsis, as well as its underlying mechanism. The acute ethanol intoxication model was simulated by intraperitoneally administering mice with 32% ethanol solution, and cecal ligation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…SPHK1, a kinase in sphingolipid metabolism, is recognized as a critical factor in the regulation of inflammatory response and cellular immunity. 27 For example, SPHK1 promoted inflammatory responses in renal clear cell carcinoma 28 and cerebral ischemia/reperfusion injury, 29 and its reduced levels alleviated inflammatory factor release in ethanol-intoxicated septic mice 30 and was involved in the ameliorative effect of atractylenolide-1 in mice with colitis. 31 The transcriptional activation of pro-inflammatory cytokines (IL-6), chemokines, and adhesion molecules requires the activation of SPHK1.…”
Section: Discussionmentioning
confidence: 99%
“…SPHK1, a kinase in sphingolipid metabolism, is recognized as a critical factor in the regulation of inflammatory response and cellular immunity. 27 For example, SPHK1 promoted inflammatory responses in renal clear cell carcinoma 28 and cerebral ischemia/reperfusion injury, 29 and its reduced levels alleviated inflammatory factor release in ethanol-intoxicated septic mice 30 and was involved in the ameliorative effect of atractylenolide-1 in mice with colitis. 31 The transcriptional activation of pro-inflammatory cytokines (IL-6), chemokines, and adhesion molecules requires the activation of SPHK1.…”
Section: Discussionmentioning
confidence: 99%
“…However, PF-543 had no effect on Cer level, suggesting that the lack of the ability to induce apoptosis ( Byun et al, 2013 ; Wang et al, 2013 ). A recent study has proved that PF-543 reduces apoptosis in the lungs of mice after acute ethanol intoxication, and inhibits neutrophil infiltration and the release of inflammatory cytokines to reduce lung injury ( Chen et al, 2021b ). As the most effective SphK1 inhibitor so far, PF-543 can inhibit inflammation in RA model ( Deng et al, 2021 ), ulcerative colitis model ( Liu and Jiang, 2020 ) and mouse pulmonary hypertension hypoxia model ( Ha et al, 2020 ) in vivo and in vitro , mainly by inhibiting the release of inflammatory cytokines and the change of cell biological function.…”
Section: Sphingosine Kinase 1 Selective Inhibitorsmentioning
confidence: 99%
“…PF-543, a novel and selective inhibitor of SPHK1 among all the SK inhibitors, exerted potent antiproliferation and cytotoxic effects applied in multiple cancer treatments [ 24 ]. A study demonstrated that PF-543 alleviated lung injury caused by sepsis in acute ethanol intoxication rats by suppressing the SPHK1/S1P/S1PR1 signaling pathway [ 25 ]. To further characterize the oncogenic role of SPHK1 in NSCLC cells, MTT assay was performed to test the effect of PF-543 on cell survival.…”
Section: Resultsmentioning
confidence: 99%